2020
DOI: 10.1111/den.13807
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for non‐polypoid colorectal neoplasms

Abstract: The miss rate of flat advanced colorectal neoplasia is still unacceptably high, especially in the Western setting, notwithstanding the widespread implementation of quality improvement programs and training. It is well known that flat morphology is associated with miss rate of colorectal neoplasia, and that this subset of lesions often shows a more aggressive biological behaviour. Artificial intelligence (AI) applied to the detection of colorectal neoplasia has been shown to increase adenoma detection rate, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Another domain in which CADe performance has yet to be improved is the detection of non-polypoid lesions[ 32 ]. These colorectal lesions account for a large portion of missed colorectal neoplasia and may be associated with a more aggressive biological behaviour.…”
Section: Future Perspectives and Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another domain in which CADe performance has yet to be improved is the detection of non-polypoid lesions[ 32 ]. These colorectal lesions account for a large portion of missed colorectal neoplasia and may be associated with a more aggressive biological behaviour.…”
Section: Future Perspectives and Controversiesmentioning
confidence: 99%
“…These colorectal lesions account for a large portion of missed colorectal neoplasia and may be associated with a more aggressive biological behaviour. A recent review[ 32 ] has shown that among the published RCTs on CADe systems, some of them did not report the number of flat lesions included in the training sets and others did not report sub-analysis on the performance of AI specifically for flat lesions. The authors concluded that in future CADe systems, development and refinement, additional training and validation for the recognition of the individual subtypes of non-polypoid lesions, especially for non-granular lateral spreading tumors (LST-NG), is urgently needed.…”
Section: Future Perspectives and Controversiesmentioning
confidence: 99%
“…Let’s be honest! Most AI engines in colonoscopy have never been presented with enough cases of rarer but highly clinically relevant lesions, such as non-granular laterally spreading tumors or depressed invasive cancers 9 .…”
mentioning
confidence: 99%
“…Let's be honest! Most AI engines in colonoscopy have never been presented with enough cases of rarer but highly clinically relevant lesions, such as non-granular laterally spreading tumors or depressed invasive cancers [9]. Annotation-related burden is primary responsible for the persistent delay in AI implementation throughout the field of gastrointestinal endoscopy.…”
mentioning
confidence: 99%
“…Large flat or minimally elevated laterally spreading lesions are under-represented in existing training datasets but have a higher rate of covert malignancy or progression to cancer than diminutive polyps. CADe has been shown to increase the detection of diminutive polyps; however, detection of the inconspicuous laterally spreading lesions and advanced adenomas may have a greater influence on cancer risk reduction [5]. Endoscopists with high ADRs detect high rates of both advanced adenomas and diminutive polyps [6], but a recent meta-analysis of AI CADe only showed a trend toward increased detection of advanced adenomas [4].…”
mentioning
confidence: 99%